Nanoindentation: An advanced procedure to investigate osteochondral engineered tissues. (August 2019) - Boi, Marco; Marchiori, Gregorio; Berni, Matteo; Gambardella, Alessandro; Salamanna, Francesca; Visani, Andrea; Bianchi, Michele; Fini, Milena; Filardo, Giuseppe
Abstract: Osteochondral scaffolds are emerging as a promising alternative for articular cartilage regeneration, although with still controversial results. In particular, the restoration of the osteochondral interface remains an open challenge. The current available investigative procedures are not optimal to quantify the properties of this region, neither to evaluate the quality of the regenerated tissue with respect to the physiological one. This study investigates an advanced procedure able to quantitatively evaluate the mechanical gradient between stiff and compliant tissues, such as in the osteochondral region where the interface between hyaline and calcified cartilage (tidemark) plays an integral role in transferring articular loads from the compliant articular surface to the stiffer underlying bone. A series of nanoindentation line scans was performed along the tidemark - starting from hyaline and expanding across calcified cartilage - on histological sections derived from sheep osteochondral tissue regenerated by a three-layered biomimetic scaffold, as well as to the adjacent healthy tissue for comparative purposes. After an accurate assessment of the indentation parameters, a sigmoid curve-fit function was applied on the reduced modulus profiles to extract gap, width and regularity of the mechanical transition. The designed procedure succeeded in quantitatively assessing the transition between compliant and stiff regions, limiting experimental issues that generally affect the reliability of the indentation mechanical data, such as apex-blunt indenter tip effect, surface roughness, and influence of the substrate. Among the evaluated parameters, the mechanical gap highlighted the main difference between native and regenerated tissues. Thanks to the information retrievable through this procedure, this load transmission area can be further investigated, providing data to tailor osteochondral engineered tissues in the future.